Nanoscopic distribution of VAChT and VGLUT3 in striatal cholinergic varicosities suggests colocalization and segregation of the two transporters in synaptic vesicles - Cristofari, Paola; Desplanque, Mazarine; Poirel, Odile; Hébert, Alison; Dumas, Sylvie; Herzog, Etienne; Danglot, Lydia; Geny, David; Gilles, Jean-François; Geeverding, Audrey; Bolte, Susanne; Canette, Alexis; et al. (Frontiers in Molecular Neuroscience, 2022)
Striatal cholinergic interneurons (CINs) use acetylcholine (ACh) and glutamate (Glut) to regulate the striatal network since they express vesicular transporters for ACh (VAChT) and Glut (VGLUT3). However, whether ACh and Glut are released simultaneously and/or independently from cholinergic varicosities is an open question. The answer to that question requires the multichannel detection of vesicular transporters at the level of single synaptic vesicle (SV). Here, we used super-resolution STimulated Emission Depletion microscopy (STED) to characterize and quantify the distribution of VAChT and VGLUT3 in CINs SVs. Nearest-neighbor distances analysis between VAChT and VGLUT3-immunofluorescent spots revealed that 34 % of CINs SVs contain both VAChT and VGLUT3. In addition, 40 % of SVs expressed only VAChT while 26 % of SVs contain only VGLUT3. These results suggest that SVs from CINs have the potential to store simultaneously or independently ACh and/or Glut. Overall, these morphological findings support the notion that CINs varicosities can signal with either ACh or Glut or both with an unexpected level of complexity.